Physics Textbook Analysis Based On 21st Century Skills - Rima Oktafianto, Wakid; Hartono, Hartono; Sulhadi, Sulhadi (Universitas Negeri Semarang, 2019)
21st Century society not only masters conceptual knowledge, but is also required to be able to apply concepts and have a variety of life skills commonly referred to as 21st century skills. Education plays an important role in preparing students for life. One important factor in the education curriculum is textbooks. This study aims to obtain information about the level of content of 21st century skills textbooks in Physics grade X. 21st Century skills that are the focus of this research are creativity and innovation; critical thinking, problem solving, and decision making; communication; collaboration. The results showed that the Physics textbook analyzed presents critical thinking skills, problem solving, and decision making at 61.86%; communication by 15.81%; creativity and innovation by 14.88%, and collaboration by 7.44%. The data illustrates that the physics textbook analyzed more dominantly exercises critical thinking skills, problem solving, and decision making.